Mammographic changes related to different types of hormonal therapies. - Saipin Pongsatha (2018)
OBJECTIVES: To determine the effects of different types of hormone therapies (HT) on mammographic breast density changes. MATERIAL AND METHOD: Between 1999 and 2002, mammograms obtained before and 12-18 months after different types of HT in 170 women were evaluated Estrogen alone (n = 66), or estrogen in cyclic (n = 59) or continuous (n = 45) combination with progesterone were used. The baseline mammographic density was classified according to the Breast Imaging Reporting and Data Systems (BI-RADS). The serial changes observed mammographically were categorized as follows; no change, minimal change (10-25% increased density), moderate change (26-50% increased density), and marked change (> 50% increased density). Results: Twelve (7%) of the women developed an increase in parenchymal density after HT: Mammographic changes were minimal change in five (2.9%) of the women, moderate change in four (2.3%), and marked change in three (1.8%). No mammographic change was observed in women receiving cyclic estrogen-progesterone. A greater percentage of women who had undergone continuous estrogen-progesterone therapy (22.2%, 10 of 45) demonstrated more change than those who had estrogen alone (3%, 2 of 66). The difference was statistically significant (p < 0.01). Conclusion: Changes of increased density after HT was seen in only 7% of mammograms and depended on the selected hormone regimen.